The Rise of Finance and Firm Employment Dynamics - Lin, Ken-Hou (Organization Science, 2016)
This article sheds light on the ongoing employment stagnation in the United States by investigating the links between the rise of finance and firm employment dynamics during the 1982–2005 period. I argue that the rise of finance marginalized the role of labor in revenue generating and sharing processes, which led to employment stagnation among the largest nonfinancial firms in the United States. Evidence suggests that increasing investment in financial assets depresses the workforce size. The growing dependence on debt reprioritizes the order of distribution, heightening the need for workforce reduction. The increasing rewards for shareholders generate a downsize-and-distribute spiral, in which labor expense becomes a primary target of cost-cutting strategies. Further analysis indicates that production and service workers are more vulnerable to shifts associated with the rise of finance than managers and professionals.